2019
DOI: 10.3390/nu11071489
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Sulforaphane Following Ingestion of Glucoraphanin-Rich Broccoli Sprout and Seed Extracts with Active Myrosinase: A Pilot Study of the Effects of Proton Pump Inhibitor Administration

Abstract: We examined whether gastric acidity would affect the activity of myrosinase, co-delivered with glucoraphanin (GR), to convert GR to sulforaphane (SF). A broccoli seed and sprout extract (BSE) rich in GR and active myrosinase was delivered before and after participants began taking the anti-acid omeprazole, a potent proton pump inhibitor. Gastric acidity appears to attenuate GR bioavailability, as evidenced by more SF and its metabolites being excreted after participants started taking omeprazole. Enteric coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…Conversion of GR to SF (bioavailability) was calculated as percent of dose excreted in collected urine samples, and was normalized on a molar equivalence basis (moles of GR to moles of SF plus its metabolites as determined in the cyclocondensation reaction). Conversion efficiencies varied among subjects from 8.2% to 68.4% of the administered dose, which is consistent with the data we and others have previously reported on bioavailability in adults 11,68,69 . Post-dose plasma DTC levels were closely related to the time between last dose and blood draw, with lower levels at less than 2 h or more than 14 h, and higher levels between 9-10 h after the last dose (Table 1).…”
Section: Biomarkers Show Consistent Responsiveness To Sf Ex Vivo Treasupporting
confidence: 92%
“…Conversion of GR to SF (bioavailability) was calculated as percent of dose excreted in collected urine samples, and was normalized on a molar equivalence basis (moles of GR to moles of SF plus its metabolites as determined in the cyclocondensation reaction). Conversion efficiencies varied among subjects from 8.2% to 68.4% of the administered dose, which is consistent with the data we and others have previously reported on bioavailability in adults 11,68,69 . Post-dose plasma DTC levels were closely related to the time between last dose and blood draw, with lower levels at less than 2 h or more than 14 h, and higher levels between 9-10 h after the last dose (Table 1).…”
Section: Biomarkers Show Consistent Responsiveness To Sf Ex Vivo Treasupporting
confidence: 92%
“…To the best of our knowledge, it has not been established whether gut content of myrosinase-expressing bacteria varies with BMI. When active myrosinase is included in glucosinolate-rich meals as in our earlier study (25) and in that of Fahey et al (41), ITCs and ITC metabolites are rapidly produced and then absorbed in the upper digestive tract. Neither study reported a main effect of BMI.…”
Section: Discussionsupporting
confidence: 54%
“…In broccoli sprouts, two of the most abundant GLSs are glucoraphanin and glucoerucin, and myrosinase hydrolysis of these GLSs form SFN and ERN, respectively. SFN, distinguished ITCs in broccoli sprouts, is one of the most potent naturally occurring inducers of phase 2 detoxification enzymes, boost antioxidant status, and protect animals against chemically induced cancer [40,90]. Its modes of action are involved with the repressor protein Kelch-like ECH associated protein 1 (Keap1), nuclear factor erythroid 2 p45-related factor 2 (Nrf2), and genes, which contain an antioxidant responsive element (ARE) [62].…”
Section: Bioavailability Of Bioactive Compoundsmentioning
confidence: 99%